The Ford century in Minnesota - McMahon, Brian, 1945- (University of Minnesota Press, 2016)
In 1903, before the Ford Motor Company was even incorporated, Stephen Tenvoorde signed a contract to sell ?Fordmobiles? at his bicycle shop in St. Cloud, Minnesota. Four generations later, the Tenvoorde family still operates what is now the oldest Ford dealership in the world. Brian McMahon chronicles how the fortunes of the company and the state became intertwined during that century. Ford assembled Model T cars in the world?s tallest automobile plant in Minneapolis and a three-story structure in St. Paul?both still standing. These factories quickly became functionally obsolete after the development of the moveable assembly line. The hunt for a new site to build a modern, single-story plant stirred intense rivalry between Minneapolis and St. Paul. Henry Ford took a rare personal interest in the search and selected a 125-acre parcel in St. Paul overlooking the recently built High Dam on the Mississippi River, which allowed for navigation and hydroelectric power. The Twin Cities Assembly Plant would go on to manufacture millions of cars, trucks, tractors, and military vehicles until its closure in 2011.